The expression of emotion in selected modern poems - Mohd Salleh, Nurul Afifah Adila; Abd Rahim, Normaliza (Dewan Bahasa dan Pustaka, 2016)
Emotions may be expressed in several ways, be these verbal or non-verbal. At first, emotional reaction can be illustrated through a person’s physical and cognitive development and is represented by the language in the linguistic form. This study focuses on the expression of emotion in selected modern poems. The objective of this research is to identify the types of emotions and explain the effects and influences of these emotions in modern poetry. This research was conducted employing a qualitative method to analyse the content of the text. Five modern poems from selected books were used as data. The theoretical framework of Mohd Azhar Abd Hamid (2004) which revolves around the expression of emotion was used as the basis for analysis and discussion in this study. The findings reveal that the five poems studied employ language that depicts both positive and negative emotions. This study is of great importance to writers and composers of poems, in order to ensure that what they wish to express is understood and appreciated by the listener or reader of the poems.